Outcome of newborns with asymptomatic monomorphic ventricular arrhythmia. Issue 6 (4th July 2006) - De Rosa, G; Butera, G; Chessa, M; Pardeo, M; Bria, S; Buonuomo, P S; Zecca, E; Romagnoli, C
Abstract : Background: Frequent premature ventricular contractions (PVCs), couplets (CPLTs) and episodes of ventricular tachycardia are extremely rare in the neonatal population. Limited information is available with regard to clinical relevance and outcome. Objectives: To evaluate the clinical characteristics and outcomes of a group of newborns with ventricular arrhythmias without heart disease. Patients and design: Between January 2000 and January 2003, 16 newborns with ventricular arrhythmias in the absence of heart disease were studied. The newborns were divided into three groups: PVC group (n = 8), CPLT group (n = 4) and ventricular tachycardia group (n = 4). All patients underwent physical examination, electrocardiography, Holter monitoring and echocardiography at diagnosis and at follow-up (1, 3, 6 and 12 months, and yearly thereafter). Results: Mean (standard deviation, SD) age of the patients was 3 (1.19) days in the PVC group, 3.25 (0.95) days in the CPLT group and 6.5 (9.1) days in the ventricular tachycardia group. Median follow-up was 36 months (range 24–48 months). PVCs disappeared during follow-up in all the neonates, in the PVC group, at a mean (SD) age of 2.1 (1.24) months; in the CPLT group, couplets disappeared at a mean (SD) age of 6.5 (1) months. All patients with ventricular tachycardia were treated; ventricular tachycardia disappeared at a mean (SD) age of 1.7 (0.9) months. Neither death nor complications occurred. Conclusions: Ventricular arrhythmias in newborns without heart disease have a good long-term prognosis. Frequent PVCs and CPLTs do not require treatment. Sustained ventricular tachycardia or high-rate ventricular tachycardia must be treated, but the prognosis is generally favourable.